Gastrointestinal stem cells in health and disease: from flies to humans - Hongjie Li; Heinrich Jasper (Disease Models & Mechanisms, 2016)
The gastrointestinal tract of complex metazoans is highly compartmentalized. It is lined by a series of specialized epithelia that are regenerated by specific populations of stem cells. To maintain tissue homeostasis, the proliferative activity of stem and/or progenitor cells has to be carefully controlled and coordinated with regionally distinct programs of differentiation. Metaplasias and dysplasias, precancerous lesions that commonly occur in the human gastrointestinal tract, are often associated with the aberrant proliferation and differentiation of stem and/or progenitor cells. The increasingly sophisticated characterization of stem cells in the gastrointestinal tract of mammals and of the fruit fly Drosophila has provided important new insights into these processes and into the mechanisms that drive epithelial dysfunction. In this Review, we discuss recent advances in our understanding of the establishment, maintenance and regulation of diverse intestinal stem cell lineages in the gastrointestinal tract of Drosophila and mice. We also discuss the field's current understanding of the pathogenesis of epithelial dysfunctions.